Age of Onset and its Correlates in Men with Sexual Interest in Children. Issue 1 (10th December 2018) - Tozdan, Safiye; Briken, Peer
Abstract: Introduction: Current discussions in the field of sex research concern the age at which sexual interest in children occurred or awareness emerged. Aim: To investigate the age of onset (AOO) and its correlates in men with sexual interest in children. Methods: Using 2 samples (study 1, patients from an outpatient treatment center, n = 26; study 2, an online survey using 3 recruitment paths, n = 94), we assessed self-reported AOO of sexual interest in children, its flexibility, its exclusiveness, and individuals' motivation to change it. We further examined the interrelation between these variables. Main Outcome Measure: AOO as the self-reported age at which participants retrospectively felt sexually attracted to children for the first time. Results: We found broad ranges in AOO (study 1: mean 20.0 ± 10.7; study 2: mean 17.0 ± 8.7), flexibility, and exclusiveness (in studies 1 and 2, 7.7% and 22.3%, respectively, reported that their sexual interest is exclusively in children). The earlier participants felt sexually attracted to children for the first time, the more they were attracted exclusively in children and the less they perceived it to be flexible. Participants who reported rather exclusive sexual interest in children were less likely to perceive it as flexible. The more participants reported on flexibility, the more they were motivated to change it. The earlier participants of study 2 felt sexually attracted to children for the first time, the less they were motivated to change. Clinical Implications: The variety of our results indicates the contradiction of overall rules for individuals with sexual interest in children. Strength & Limitations: We included individuals with sexual interest in children from different contexts (eg, forensic vs non-forensic). Our results are in line with previous findings. However, both studies included rather small samples, limiting generalizability. There is not yet consent about how to operationalize AOO. Conclusion: We recommend a differentiated perspective on individuals with sexual interest in children and on different forms of pedophilia in the diagnostic construct.